1998
DOI: 10.1103/physrevb.58.6585
|View full text |Cite
|
Sign up to set email alerts
|

Reversible depression in theTcof thin Nb films due to enhanced hydrogen adsorption

Abstract: The effect of large hydrogen concentrations ͑Ϸ30% atomic͒, on the superconducting transition temperature T c of Nb films is discussed. The hydrogen is incorporated in solutionlike phases which occur at these concentrations because the ͑␣ to ␤͒ hydride transition in these films is suppressed. X-ray-diffraction data show an asymmetric expansion of the ͓110͔ Nb interplanar spacing. This can be as high as a 6-8 % expansion perpendicular to the plane of the film for the addition of ϳ70% hydrogen, with only a 1-2 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Bulk Nb is generally known to contain hydrogen atoms and to change its characteristics [8]. For thin Nb films, Jisrawi et al reported that superconductive properties are degraded by hydrogen incorporation [5]. According to their data, the superconductive critical temperature decreases by about 0.5 to 1.0 K when Nb film includes 5 at% hydrogen.…”
Section: A Interpretation Of Changesmentioning
confidence: 99%
“…Bulk Nb is generally known to contain hydrogen atoms and to change its characteristics [8]. For thin Nb films, Jisrawi et al reported that superconductive properties are degraded by hydrogen incorporation [5]. According to their data, the superconductive critical temperature decreases by about 0.5 to 1.0 K when Nb film includes 5 at% hydrogen.…”
Section: A Interpretation Of Changesmentioning
confidence: 99%
“…The incorporation of impurity atoms into niobium can cause a significant reduction of T c , which has been demonstrated for hydrogen dissolved interstitially in b.c.c. niobium [12]. Furthermore, several niobium hydride phases are not superconducting above 1-2 K [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned impurities are problematic for SRF cavities because they reduce the thermal conductivity of niobium, thereby reducing its ability to dissipate heat during rf operation [7]. Furthermore, dissolved oxygen [8] and hydrogen [9,10] are known to decrease the superconducting transition temperature of niobium at concentrations of a few atomic percent.…”
Section: Introductionmentioning
confidence: 99%